OPTIMASI KINERJA AKUSTIK MASJID AL-IRSYAD SATYA KOTA BARU PARAHYANGAN - Rachmasari P., Nabila; Subagio, Irma (Jurnal Riset Arsitektur, 2024)
Abstract - The mosque is a place of worship for Muslims. Activities held at the mosque consist of congregational prayers, sermons, recitations, weddings and discussions forums. These activities are the kinds that require voice clarity so that the acoustics in the mosque are important. Al-Irsyad Mosque Kota Baru Parahyangan is a mosque designed by Urbane which has a porous wall design with good natural ventilation in mind. However, the porous walls in the mosque can potentially reduce the quality of the acoustical performance that occurs in the interior. Thus, the acoustic performance of Al-Irsyad Mosque in Kota Baru Parahyangan is interesting to be studied. The purpose of this study was to determine the acoustic performance of the Al-Irsyad Mosque in Kota Baru Parahyangan based on objective parameters, and what efforts can be made to optimize the acoustic performance if found not optimal. The research uses quantitative research methods. Quantitative research was carried out by conducting a literature study to find out theories about mosque acoustics, and field observations for data collection, as well as field measurements to determine the acoustical condition of the mosque. The data collected is acoustic quality measurement data based on acoustic objective parameters. The data then goes through the analysis stage to determine the acoustic performance of the mosque, and an optimization stage is carried out using the I-SIMPA simulation software if the performance is found to be non-optimal. The results showed that the acoustic performance of the mosque was still below the standard, both based on the sound distribution and the acoustic quality of the inner room itself. It was concluded that the acoustic performance of the space in the mosque is influenced by the porous building envelope and also the use of the mosque's sound system. The optimization stage is carried out by simulating the acoustical performance on I-SIMPA simulation software, by modifying the material as needed. Keywords: Acoustic Performance, Al-Irsyad Mosque, Kota Baru Parahyangan, Objective Parameters, Porous Walls, I-SIMPA Simulation.